Vibration Monitoring Standards Connected to the Use of Explosives in Different Countries - Johan Finsteen Gjødvad; Mathias Jern (International Society of Explosives Engineers)
The paper is part of the ongoing work of the Environmental committee of EFEE. To assist the European experts working with explosives one of the aims is to improve the common knowledge of similarities and differences between national legislation, standards or guidelines on vibration monitoring and other environmental monitoring during blasting in Europe and abroad. This has been done by use of an online survey through the most of 2018. Questions have been raised on vibration monitoring during blasting. The existence of norms, guidelines or standards and how they are used. Even though the questions have been kept at a high level they are formed to try to map the different national standards use of such things as frequency, guidance on monitoring position, distinction between different types of structures, requirement to the equipment and more. Furthermore a few initial questions have been raised on other environmental monitoring relevant for blasting. The respondents are national, cooperate or individual members of EFEE. The answers are experts in the use of explosives and vibration-monitoring in their respective countries. More than 60 have answered the questionnaire from 29 different countries. Mainly European as well as other nations including India, Israel, Nigeria, Saudi Arabia, UAE, USA, Greenland and Hong Kong. By analysing the incoming answers, the differences and similarities in vibration monitoring of the respondents has been clarified and mapped. Where possible other environmental monitoring has also been analysed. Where needed the different guidelines, standards and regulations have been visited to verify the answers and further elaborate on the comparison.